Modelo matemático de un reactor tubular modulable que permita la reducción de alquitranes por medio del craqueo catalítico en el gas de síntesis generado en la gasificación de biomasa (2022)
This paper presents the analysis and results of a mathematical model describing an indirectly heated fixed-bed reactor for the reduction of the concentration of tars present in the synthesis gas generated in biomass gasification by catalytic cracking. The reactor performance is evaluated by varying parameters such as it, mass flow, syngas temperature and reactor geometrical conditions, generating information to determine design parameters that increase the reactor performance. The model is developed in Python and was solved by the finite difference method in 2 dimensions. As a result of the simulation, the appropriate synthesis gas temperature to reduce the tar concentration by 99% is 550 °C.